SERANGGA-SERANGGA yang BERASOSIASI pada TANAMAN CABAI KERITING (Capsicum annum L.) di KELURAHAN KAKASKASEN II KECAMATAN UTARA - Brigitha M. Gobel; Robert W Tairas; Juliet M.E. Mamahit (COCOS, 2017)
ABSTRACT Chilies curly contains nutrients necessary for human health. In an effort to increase crop production curly chili farmers are often constrained by insects that exist in the land for planting chilli curls considered everything is pests and diseases. In an effort to increase crop production curly chili farmers are often constrained by insects that exist in the land for planting chilli curls considered everything is pests and diseases. This study aimed to determine the insects associated in pepper curly (C. annuum) in the Village of North Tomohon sub district Kakaskasen II and the research conducted over six months from June to November 2016. With two different planting patterns are monoculture and polyculture. The method used is descriptive quantitative method to conduct a field survey. Sampling was insect that is directly using the killing bottle containing 70% alcohol. Insects found are: Ordo Lepidoptera (Famili Noctuidae), Ordo Orthoptera (Famili Tettigoniidae), Ordo Homoptera (Familli Cicadellidae), Ordo Hemiptera (Aphididae), Ordo Coleoptera (Famili Coccinelidae, Scarabaeidae, Curculionidae dan Staphylinidae), Ordo Diptera (Famili Dolichopodidae dan Syrphidae), Ordo Hymenoptera (Famili Apidae).